Aortic root reimplantation in patients with bicuspid and tricuspid aortic valve: a systematic review - Kokorin, A.V.; Aminov, V.V.; Lukin, O.P.; Bogachev-Prokophiev, A.V. (Patologii͡a︡ krovoobrashchenii͡a︡ i kardiokhirurgii͡a, 2024)
Introduction: Valve-preserving operations are gaining popularity in the surgical treatment of aortic root aneurysms in patients with both tricuspid aortic valve (TAV) and bicuspid aortic valve (BAV). Most studies are focused on the results of valvepreserving procedures in patients with TAVs. Objective: The study takes a comparative assessment of clinical results on aortic root reimplantation in patients with TAV and BAV. Methods: The systematic review was accomplished according to the PRISMA 2020 criteria. Search for published papers involving comparison of the results on the valvepreserving aortic root reimplantation in patients with TAV and BAV was conducted in three main electronic databases, namely Medline [PubMed], Web of Science, and Google Scholar. The review only included studies, which involved patients of both groups, differed by the anatomy of the valve; studies based on one examination group were excluded. Results: We revealed that 13 articles met the inclusion criteria. In total, the review involved the treatment results of 3,191 patients, of whom 608 had a BAV and 2,583 had a TAV; patients of comparison groups were similar by sex and age. In most studies, hospital mortality did not exceed 1%. Patients with BAV and TAV showed no significant differences in freedom from aortic regurgitation (AR) ≥ II and long-term survival in 5, 10, 15, and 20 years. However, certain studies noted that patients of the BAV group had a significantly higher reoperation rate than those with TAV (p = 0.026 and p = 0.002). Conclusion: Reimplantation provides excellent survival for long-term follow-up periods with a low risk of reoperation and recurrence of aortic regurgitation in patients both with TAV and BAV. Received 4 July 2024. Revised 15 September 2024. Accepted 19 September 2024. FundingThe research was carried out within the framework of the grant of the Russian Science Foundation No. 23-15-00434. Conflict of interestThe authors declare no conflict of interest. Contribution of the authorsThe authors contributed equally to this article.